Migration, Health and Ethnicity in the Modern World
XII, 213 p.
Keywords: The volume focuses on the relationship between migration, health and illness in a global context from c.1820 to the present day. It takes a wide range of finely-grained case studies to examine epidemic disease and its containment, chronic illness and mental breakdown and the health management of migrant populations in the modern world.